Work-related injuries among farmers: a cross-sectional study from rural Nepal. Issue 1 (December 2016) - Bhattarai, Devendra; Singh, Suman; Baral, Dharanidhar; Sah, Ram; Budhathoki, Shyam; Pokharel, Paras
Abstract Background Agriculture work is one of the most hazardous occupations across countries of all income groups. In Nepal, 74 % of people are working in the agricultural sector. This study aims to identify patterns and factors associated with injuries among farmers of rural Nepal. Methods A community-based cross-sectional study was conducted in a rural village in eastern Nepal. House to house visit was done to collect data from the farmers. The study included 500 farmers from Shanishchare village in Morang district of Nepal. A pre-tested semi-structured questionnaire was used to collect data on socioeconomic profile, agriculture work and injury. Prevalence of injuries among farmers in the last 12 months was calculated along with factors associated with the injuries. Results The overall prevalence of work- related injuries among farmers was 69 % in the last 12 months. Common injuries among the farmers were cuts (79.7 %), puncture wound (11.3 %) and laceration (7.5 %). Hand tools were responsible for most of the injuries followed by slipping at work, sharp instruments, animals and fall from height. Upper limb injury comprised of 67 % of all injuries and the most involved part was fingers (43 %). The average number of years worked in farming by the respondents was 23.6 ± 13.6 years. Age and working experience of the farmers was found to be significantly associated with the occurrence of injuries among the farmers. Conclusions The prevalence of injury among farmers in this study was high. Further research is needed to identify interventions to reduce the agricultural injuries in Nepal.